2022
DOI: 10.3934/mbe.2022223
|View full text |Cite
|
Sign up to set email alerts
|

Low-carbon strategies in dual-channel supply chain under risk aversion

Abstract: <abstract><p>In a low-carbon supply chain (LCSC) constructed by a single manufacturer and a single retailer, three decision-making models are established by introducing channel preference attributes. That is, a single sales channel model, an online and offline dual channel model, and a dual channel model in which the manufacturer share revenue with her retailer. Using the mean variance (MV) method to characterize the risk aversion utility function of the manufacturer and the retailer, the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…(5) It is assumed that the manufacturer has the same wholesale price in the dual channel w r � w p � w. at is because the retailer and platform play the same role for the manufacturer [34,35]. (6) e cost of carbon abatement for manufacturers is C � 1/2ns 2 , assuming n � 1 for simple calculation [27]. (7) Consumers are heterogeneous in their preference for the different channels, which are uniformly distributed between 0 and 1.…”
Section: Notations and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) It is assumed that the manufacturer has the same wholesale price in the dual channel w r � w p � w. at is because the retailer and platform play the same role for the manufacturer [34,35]. (6) e cost of carbon abatement for manufacturers is C � 1/2ns 2 , assuming n � 1 for simple calculation [27]. (7) Consumers are heterogeneous in their preference for the different channels, which are uniformly distributed between 0 and 1.…”
Section: Notations and Assumptionsmentioning
confidence: 99%
“…Many scholars have observed this phenomenon and conducted a series of research on such dual-channel supply chain. Li et al established a traditional low-carbon dual-channel supply chain consisting of a manufacturer's direct channel and o ine channel and found that dual-channel development contributes to growing the pro ts of the manufacturer under a limited risk aversion environment [6]. Zhou et al investigated the joint emission reduction strategies in a dual-channel supply chain and found that involvement of the manufacturer's direct channel contributes to heightening emission reduction e orts of manufacturer [7].…”
Section: Introductionmentioning
confidence: 99%
“…Expected utility (EU) [ 7 ], mean variance (MV) and conditional value at risk (CVaR) [ 8 ] are three common measures of risk aversion. Compared with EU and CVaR methods, MV has advantages in modeling risk aversion because it can transform random problems into deterministic approximate problems [ 9 ]. Therefore, we consider the MV method for modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Tere have been many research studies on the procurement of risk-neutral emergency materials [31]. However, it is rare to introduce the risk attitude of decision makers into the emergency procurement [32][33][34]. Due to the economic downturn in recent years, the risk aversion has attracted the attention of many scholars.…”
Section: Introductionmentioning
confidence: 99%